Abnormal Blood Glucose as a Prognostic Factor for Adverse Clinical Outcome in Children Admitted to the Paediatric Emergency Unit at Komfo Anokye Teaching Hospital, Kumasi, Ghana - Emmanuel Ameyaw; Kwame Amponsah-Achiano; Peter Yamoah; Jean-Pierre Chanoine (International Journal of Pediatrics)
Dysglycaemia (hyper- or hypoglycaemia) in critically ill children has been associated with poor outcome. We compared the clinical outcomes in children admitted to Pediatric Emergency Unit (PEU) at Komfo Anokye Teaching Hospital (KATH) for acute medical conditions and presenting with euglycaemia or dysglycaemia. This is a prospective case matching cohort study. Eight hundred subjects aged between 3 and 144 months were screened out of whom 430 (215 with euglycaemia and 215 with dysglycaemia) were enrolled. The median age was 24 months (range: 3–144 months). In the dysglycaemia group, 28 (13%) subjects had hypoglycemia and 187 (87%) had hyperglycemia. Overall, there were 128 complications in 116 subjects. The number of subjects with complications was significantly higher in dysglycaemia group (n=99, 46%) compared to euglycaemia group (n=17, 8%) (P<0.001). Forty subjects died out of whom 30 had dysglycaemia (P=0.001). Subjects with dysglycaemia were 3 times (95% CI: 1.5–6.0) more likely to die and 4.8 times (95% CI: 3.1–7.5) more likely to develop complications (P=0.001). Dysglycaemia is associated with increased morbidity and mortality in children with acute medical conditions and should lead to intensive management of the underlying condition.